Freshening of Antarctic Bottom Water in the Indian Ocean sector of Southern Ocean. (August 2015) - Anilkumar, N.; Chacko, Racheal; Sabu, P.; George, Jenson V.
Abstract: Recent observations reveal a rapid reduction in salinity and density of Antarctic Bottom Water (AABW) in the Indian Ocean sector of Southern Ocean. Previous studies have shown fast freshening of AABW since 1995, but an increased rate of freshening from 2006 to 2010 was exhibited in the present study by both ECMWF (ORAS4) reanalysis data as well as in-situ data. During the same period the degrees of change observed in the AABW were more predominant in the in-situ data, becoming warmer (~0.05 °C), fresher (~0.01) and lighter (~0.01 kg m −3 ). Between 2006 and 2010 the height of fresh water added per unit area for 500 m thickness (4000–4500 m) was 2.2 cm per annum (cm a −1 ). The AABW observed in the present study could have originated from Weddell Sea or Cape Darnley polynya. The decadal changes indicate an enhanced sea-ice formation, due to increased positive phases of Southern Annular Mode (SAM), which may have led to the increase in fresh water input, resulting in freshening of AABW.